From confrontation to civil war : conflict management in the Satsuma Rebellion, 1877 : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Japanese at Massey University - Tuffley, Peter (Massey University, 1997)
The orthodox view of the outbreak of the 1877 Satsuma Rebellion characterises those actions of Japan's central government which provoked the insurrection as mistakes made in an effort to defuse the confrontational relationship that had developed between the government and Kagoshima prefecture. This thesis offers a critical reappraisal of this view, and examines the hypothesis—suggested by the Japanese historians Inoue Kiyoshi and Môri Toshihiko, as well as by the historical novelist Shiba Ryôtarô—that those actions were intentionally provocative, with the aim of promoting a military resolution of the confrontation. Rather than an accidental outbreak of violence, the Rebellion and the ensuing civil war are considered, in Clausewitzian terms, as "a continuation of (domestic) politics, with the addition of other means", in which the transition from non-violent to military confrontation was, arguably, engineered by the government leadership (in particular by the de-facto leader of the Meiji oligarchy, Ôkubo Toshimichi), just as Bismarck engineered the outbreak of the Franco-Prussian War by means of the Ems Telegram, in order to bring about armed conflict without taking the role of aggressor. The thesis also examines the influence of unforced strategic error on the course of the civil war in its early stages. This leads to a reappraisal of the orthodox view that the imperial forces were never in danger of defeat, and to the conclusion that the Rebellion could well have succeeded but for major strategic error on the part of the rebel leaders.
Keywords: Satsuma Rebellion, 1877; Japan -- History; Meiji period, 1868-1912